2020
DOI: 10.2147/ott.s232848
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA PART1 Exerts Tumor Suppressive Functions in Glioma via Sponging miR-190a-3p and Inactivation of PTEN/AKT Pathway</p>

Abstract: Background: Glioma is the most commonly diagnosed primary brain tumor. Dysregulation of long non-coding RNA (lncRNA) is associated with initiation and development of various cancer types including glioma. Methods: The relative expression of lncRNA was analyzed by real time-quantitative polymerase chain reaction (RT-qPCR). Cell counting kit (CCK-8) and flow cytometry analysis were applied to explore the role of prostate androgen-regulated transcript 1 (PART1) in glioma cell lines. Luciferase reporter assay, Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
(39 reference statements)
1
25
0
Order By: Relevance
“…In detail, PART1 acted as oncogenic factors in bladder cancer 32 and hepatocellular carcinoma, 33 while it acted as tumor suppressors in oral squamous cell carcinoma 22 and glioblastoma. 34,35 However, the biological effects and underlying mechanisms of PART1 on TSCC were unclear. In our study, we found that the expression levels of lncRNA PART1 and miR-503-5p were inversely correlated with each other in TSCC tissues, and overexpression of PART1 in TSCC cell lines inhibited miR-503 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In detail, PART1 acted as oncogenic factors in bladder cancer 32 and hepatocellular carcinoma, 33 while it acted as tumor suppressors in oral squamous cell carcinoma 22 and glioblastoma. 34,35 However, the biological effects and underlying mechanisms of PART1 on TSCC were unclear. In our study, we found that the expression levels of lncRNA PART1 and miR-503-5p were inversely correlated with each other in TSCC tissues, and overexpression of PART1 in TSCC cell lines inhibited miR-503 expression.…”
Section: Discussionmentioning
confidence: 99%
“…37 PART1 could mediate the secretion of cytokines and metastasis of tumor cells to affect cancer progression. 15 The expression of PART1 was impeded in glioma tissues and exerted suppressive functions on malignant behavior by targeting miR-190a-3p in glioma cell lines.- 35 Similarly, PART1 was down-regulated in TSCC tissues of patients and a higher level of PART1 was positively correlated with better prognosis. 15 Different miRNAs showed conversed effects in TSCC, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PART1 plays a tumor suppressive function in gliomas [35], but has a procancer effect in bladder cancer [36], non-small-cell lung cancer [37], and colorectal cancer [38]. hsa-miRNA-429 plays an inhibitory role in a number of tumors [39][40][41], including glioma [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has identified a binding site on lncRNA PART1 for miR-190a-3p ( 26 ). Therefore, in the present study, Starbase version 2.0 ( http://starbase.sysu.edu.cn/ ) was used to verify the potential interaction between lncRNA PART1 and miR-190a-3p, which was confirmed using Dual-luciferase reporter assay.…”
Section: Methodsmentioning
confidence: 99%
“…miRNAs serve vital roles in numerous diseases by regulating gene expression, cell proliferation, inflammation, apoptosis and invasion (22)(23)(24), such that miRNA dysregulation has been previously associated with a number of human diseases (25). A recent study also revealed that miR-190a-3p is involved in glioma (26), where it was indicated that lncRNA PART1 exerts tumor suppressive effects by sponging miR-190a-3p, suggesting a regulatory effect of lncRNA PART1 on miR-190a-3p function (26). However, the role of miR-190a-3p in IDD progression is not completely understood and whether lncRNA PART1 can affect IDD by regulating miR-190a-3p remains unclear.…”
Section: Role Of Lncrna Part1 In Intervertebral Disc Degeneration Andmentioning
confidence: 99%